2019
DOI: 10.1038/s41388-019-0929-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of mutant IDH1 by DS-1001b ameliorates aberrant histone modifications and impairs tumor activity in chondrosarcoma

Abstract: Chondrosarcoma is the second most common malignant bone tumor. It is characterized by low vascularity and an abundant extracellular matrix, which confer these tumors resistance to chemotherapy and radiotherapy. There are currently no effective treatment options for relapsed or dedifferentiated chondrosarcoma, and new targeted therapies need to be identified. Isocitrate dehydrogenase (IDH) mutations, which are detected in~50% of chondrosarcoma patients, contribute to malignant transformation by catalyzing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…Suijker et al have reported that CpG island methylation and histone H3K4, -9, and -27 trimethylation levels remained unchanged upon specific inhibition of IDH1 mut in chondrosarcoma cells [16]. On the other hand, Nakagawa et al recently demonstrated that selective inhibition of IDH1 mut significantly reduced the levels of H3K4, -9 trimethylation and promotes normal chondrocyte differentiation [40]. This discrepancy suggests that IDH1 mut may promote chondrosarcoma growth through some mechanisms beyond the well-characterized epigenetic effects in other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Suijker et al have reported that CpG island methylation and histone H3K4, -9, and -27 trimethylation levels remained unchanged upon specific inhibition of IDH1 mut in chondrosarcoma cells [16]. On the other hand, Nakagawa et al recently demonstrated that selective inhibition of IDH1 mut significantly reduced the levels of H3K4, -9 trimethylation and promotes normal chondrocyte differentiation [40]. This discrepancy suggests that IDH1 mut may promote chondrosarcoma growth through some mechanisms beyond the well-characterized epigenetic effects in other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in SOX9 in DDCS in comparison to high-grade chondrosarcoma indicates that SOX9 reduction may support the progression into dedifferentiated stages or could even be a requirement for it. Other in vitro studies recently showed, that tumor progression involved SOX9 and CDKN1C repression in different chondrosarcoma cell lines [ 12 ]. Posttranscriptional regulation of SOX9 via miRs, i.e., miR-145, might be involved in this mechanism as reported by Mak et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the versatility of SOX9 could be a combination of post-transcriptional modifications, the type of tissue in which it is expressed and certain binding partners. To date, only very few studies have been published on the detailed role of SOX9 during chondrosarcoma development and progression [ 12 ]. The latest studies emphasize the direct crosstalk between SOX9 and a mutation of isocitrate dehydrogenase (IDH) 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant IDH1 has become a very attractive therapeutic target in the field of antitumor drug discovery, and several pharmaceutical companies have attempted to develop novel small molecule inhibitors against mutant IDH1. So far, several small molecule inhibitors targeting mutant IDH1 enzymes have been developed (see Figure 1) (Rohle et al, 2013;Davis et al, 2014;Deng et al, 2015;Kim et al, 2015;Okoye-Okafor et al, 2015;Law et al, 2016;Chaturvedi et al, 2017;Xie et al, 2017;Popovici-Muller et al, 2018;Nakagawa et al, 2019;Caravella et al, 2020;Konteatis et al, 2020). Some of these have been studied in various preclinical models, and some are currently being evaluated in phase I/II clinical studies for different tumor pathologies with IDH1 enzyme mutations.…”
Section: Introductionmentioning
confidence: 99%